Knowledge About HIV/Aids with Compliance To Provider Initiated Testing and Counseling In 1st Trimester Pregnant Women - Ni Made Ayu Wulandari; Lina Darmayanti Bainuan; Sabrina Farani (Syntax Literate, 2022)
Human Immunodeficiency Virus-Aquaired Immunodeficiency syndrom (HIV-AIDS) was one of disease that got special attention from the health world. The research was based on a large number of mothers still do not understand deeply about HIV/AIDS and do not follow PITC (Provider Initiated Testing and Counceling) so as not to be detected early possibility of the risk of transmission of HIV/AIDS from mother to baby. The purpose of this research was to know the correlation of knowledge about HIV/AIDS with the compliance to Provider From Testing And Counseling (PITC) on 1st trimester of pregnant women. The design used in this study was analytic approach with cross sectional correlation. The population in this research was all 1st trimester pregnant women in PPM (Private Practice Midwife) Mrs "W" of the Yehsumbul Village, Mendoyo sub district, Jembrana Regency, Bali province in December 2021 a number of 30 persons. This research sampling was total sampling. Data analysis used Spearman's rho test. The results suggested that nearly half (26.7%) of respondents who had less knowledge, had negative behavior in the following Provider From Testing and Counseling (PITC). The results of the analysis of data obtained pvalue = 0.002 or less of Î± = 0.05 means there was a correlation between the knowledge about HIV/AIDS with the compliance to PITC on 1st trimester pregnant mothers In PPM Mrs "W" Yehsumbul Village, Mendoyo sub district, Jembrana, Bali province Year 2021. Based on the results of the research, then the Midwife must provide more intense communication, counceling, and education to pregnant women in 1st trimester of the ANC with integrated Provider From Testing and Counseling (PITC).